Mountains and lowlands: Ancient Iran and Mesopotamia - Collins, Paul (Ashmolean Museum, University of Oxford, 2016)
Ancient Mesopotamia and Iran are usually treated separately or as part of a much broader 'Ancient Near East'. However, the developments that lie at the root of our own world - farming, cities, writing, organised religion, warfare - were forged in the tensions and relations between the inhabitants of lowland Mesopotamia (ancient Iraq) and the highlands of Iran. Mountains and Lowlands explores this relationship providing a detailed but accessible account covering the period 6000 BC-AD 650, from the development of the first agricultural communities to the coming of Islam. The story is told through the superlative Ancient Near Eastern collections in the Ashmolean Museum, Oxford, supplemented by images of photographs of archaeological sites and of iconic pieces in other collections including the Louvre, Paris. The discussion is further supported by six maps commissioned especially for this publication